Should a 1% gradient be used to equate the metabolic cost between treadmill and overground running? - Mattia Nolè; Gian-Andri Baumann; Christina M. Spengler; Fernando G. Beltrami (Bern Open Publishing, 2024)
Introduction Running on a motorized treadmill offers the possibility of precise adjustments in speed as well as more complex monitoring of athletes. On the other hand, the lack of wind resistance compared with outdoor running introduces a possible significant deviation from the expected metabolic cost of running at higher speeds. The literature offers contrasting views on the topic, with older studies suggesting a lower metabolic cost for treadmill running and vice-versa for newer investigations. Nonetheless, a recommendation that treadmills use a 1% inclination gradient to account for the lack of wind resistance remains very influential in the field. We therefore investigated whether cardiorespiratory responses differ between running on a motorized treadmill with a 1% incline compared with running outdoors on a running track at a similar speed. Methods Fourteen highly trained male athletes (age 28 ± 5 years, height 180 ± 6 cm, body mass 70 ± 6 kg and peak oxygen consumption, V̇O2peak, 64 ± 4 mL kg-1･min-1) visited the laboratory on three different occasions, separated at least by 72 h. On the first day, participants performed an incremental running test to determine V̇O2peak and to familiarize themselves with the laboratory settings and equipment. On each of the two subsequent testing days, participants performed, after standardized warm-up, a 5-min run at 14 km･h-1 on either the treadmill (Pulsar It 3P, H/P Cosmos, Germany) or the track, in randomized order. Feedback regarding pacing on the track was given every 200 m. Gas exchange and heart rate were monitored throughout the runs using a portable metabolic cart (Metamax 3B, Cortex, Germany) and a connected heart rate monitor (Polar H10, Polar, Finland). In both conditions, the metabolic cart was carried by the participants using a vest provided by the manufacturer. Comparisons between conditions were performed using paired t-tests. A separate group of 4 individuals performed a set of two runs on the treadmill at 14 km･h-1 (in balanced order), once with 1% incline and once with 0% incline, to investigate the effect of the gradient on V̇O2. Results The results revealed a significant increase in the cardiorespiratory response on the treadmill compared with the track for V̇O2 (+12.6 ± 5.5%, p < 0.001, Dz = 2.6), heart rate (+5.5 ± 3.7%, p < 0.001, Dz = 1.5), and minute ventilation (+15.0 ± 0.1%, p < 0.001, Dz = 2.6). Data from the additional four participants showed that a 1% gradient increased V̇O2 by 4.4 ± 2.4% (p = 0.026) compared with a 0% gradient. Discussion/Conclusion This study shows that running on this particular treadmill model induces significantly higher cardiorespiratory responses compared with outdoor running, and that setting the incline to 1% significantly adds to this difference, instead of dampening it. These findings challenge the widely held assumption that treadmills should be set at 1% incline to yield equivalent cardiorespiratory responses to overground running. Each laboratory should test their unique settings to ascertain whether corrections based on incline are necessary.